CO-assisted ex-situ chemical activation of Pt-Cu/C oxygen reduction reaction electrocatalyst. (20th May 2019) - Gatalo, Matija; Moriau, Leonard; Petek, Urša; Ruiz-Zepeda, Francisco; Šala, Martin; Grom, Matic; Galun, Timotej; Jovanovič, Primož; Pavlišič, Andraž; Bele, Marjan; Hodnik, Nejc; Gaberšček, Miran
Abstract: In the future, low-temperature proton exchange membrane fuel cells (PEMFC), together with batteries, are expected to compete and eventually replace conventional combustion engines in the automotive industry. Currently, the most promising strategy towards cost-effective and highly-active oxygen reduction reaction (ORR) electrocatalysts seems to be alloying of Pt with less expensive and less noble 3d transition metals (Cu, Co and Ni, …). A crucial issue to be resolved in the near future is, however, to bridge the gap between the remarkable activities measured on the laboratory scale with thin film rotating disk electrode (TF-RDE) and the industrial membrane electrode assembly (MEA). In the case of Pt-Cu alloy, one of the major reasons for this difficulty is inadequate removal of unstable Cu or in other words, improper 'activation'. Inadequately removed Cu can act as an impurity by poisoning the Pt surface via the well-known underpotential deposition (UPD) interaction, resulting in the inhibition of ORR performance. Due to highly favourable experimental conditions, in-situ electrochemical activation ( in-situ EA) in TF-RDE setup masks many of the issues one experiences when trying to do the same ex-situ . Thus, matching the ORR performance obtained after in-situ EA with ex-situ CA in the case of Pt-Cu system has not been properly addressed so far. Based on a deeper understanding of in-situ EA of our in-house designed Pt-Cu/C electrocatalyst we here demonstrate development of carbon monoxide (CO) assisted ex-situ CA method. By using this gram scale ex-situ CA method, we for the first time show that a Pt-Cu system can achieve very high ORR performances in TF-RDE setup without any need for the use of in-situ EA. Graphical abstract: Image 1